1997
DOI: 10.1002/(sici)1096-9861(19971006)386:4<661::aid-cne11>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Life-span dendritic and spine changes in areas 10 and 18 of human cortex: A quantitative golgi study

Abstract: Dendritic neuropil is a sensitive indicator of the aging process and may exhibit regional cortical variations. The present study examined regional differences and age-related changes in the basilar dendrites/spines of supragranular pyramidal cells in human prefrontal (area 10) and secondary occipital (area 18) cortices. Tissue was obtained from the left hemisphere of 26 neurologically normal individuals ranging in age from 14 to 106 years (M(age) = 57 +/- 22 years; 13 males, 13 females). In tissue prepared by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
250
3
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(270 citation statements)
references
References 155 publications
(176 reference statements)
14
250
3
3
Order By: Relevance
“…Recently, Jacobs and colleagues revealed systematic differences in the maturation rate of pyramidal cells in different cortical areas (Travis et al, 2005), confirming and extending their initial observations in V2 and gPFC (Jacobs et al, 1997). Moreover, dendritic and spine loss is a common occurrence in aging (Nakamura et al, 1985;Anderson and Rutledge, 1996;Duan et al, 2003).…”
Section: Methodological Considerationsmentioning
confidence: 57%
“…Recently, Jacobs and colleagues revealed systematic differences in the maturation rate of pyramidal cells in different cortical areas (Travis et al, 2005), confirming and extending their initial observations in V2 and gPFC (Jacobs et al, 1997). Moreover, dendritic and spine loss is a common occurrence in aging (Nakamura et al, 1985;Anderson and Rutledge, 1996;Duan et al, 2003).…”
Section: Methodological Considerationsmentioning
confidence: 57%
“…This is to be expected, as glucose metabolism is thought to be an indirect measure of the number of synapses in the cortex and levels of synaptophysin have been shown to correlate with glucose metabolism (Rocher et al 2003). Finally, the decrease in synapse density late in adolescence corresponds well with the increasing ability to perform certain prefrontal cortical-dependent tasks (Casey et al 2000), A previous study in the human suggested that supragranular pyramidal neuron spine density, a measure of excitatory synapses, continues to decrease beyond age 20 and does not plateau at the adult level until much later in life, around age 40, at least in prefrontal area 10 and occipital area 18 (Jacobs et al 1997). This would suggest that if we were to continue to examine synaptic marker levels in adults over age 25, their levels would continue to decrease until the plateau corresponding to adult levels is attained.…”
Section: Discussionmentioning
confidence: 91%
“…While there are higher levels of these proteins in the young, regional decrease in protein levels may reflect synaptic changes, and particularly the loss or dysfunction of dendritic spines occurring in aging [26]. In this regard, synaptic density has been shown to be decreased in the hippocampus from old compared to young subjects [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we compared the protein expression of cPLA 2 and COX-2 in specific brain regions associated with cognitive function and motor coordination (frontal pole, hippocampus, and cerebellum) in normal healthy Rhesus monkeys at three distinct ages: young (2-5 years), middle aged adult (8-11 years) and old (23 years). Based on the evidence of loss of dendritic spines [26], drebrin [24], and reduced markers for neurotransmission [11,34,46] with aging suggesting synaptic loss, we hypothesize that cPLA 2 and COX-2 protein expression, localized at post-synaptic sites, is decreased in old compared to young monkeys.…”
Section: Introductionmentioning
confidence: 95%